Shanghai Cooperation Organization and Turkey Relations - Emre Rıfat Güpgüpoğlu (Department of Political Science - Universitas Sains Al-Qur’an, 2019)
At the beginning of the 1990s, collapsing of the USSR caused huge disappointment also political disorder and problems. To solve treacherous conditions and border disputes, joint actions were implemented by China and Russia. As a result, the Shanghai Cooperation Organization was established. On the other side of Asia, Turkey has been trying to become a member of the European Union. Although Turkey has put extraordinary effort, European Countries have not accepted Turkeys’ application. As a reflection, Turkey has started to find alternatives and headed to east to vary her options. Turkey requested to apply the SCO. The membership process is ongoing. Becoming a member of SCO has challenges and opportunities for both Turkey and SCO.